2019
DOI: 10.33119/gn/108607
|View full text |Cite
|
Sign up to set email alerts
|

Technical Efficiency and Productivity Growth of Polish Crop Farms

Abstract: Efektywność techniczna i produktywność polskich gospodarstw rolnych specjalizujących się w uprawach polowych 1 Streszczenie: W niniejszym artykule zaprezentowano analizę porównawczą wyników dotyczących efektywności technicznej oraz produktywności polskich gospodarstw rolnych, uzyskanych przy wykorzystaniu stochastycznych modeli granicznych (SFM) oraz nieparametrycznej metody DEA. Zastosowanie alternatywnych podejść dostarcza nowych informacji na temat procesu produkcyjnego oraz wskazuje na konsekwencje stosowa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…Our results are in line with findings from other studies of European examples in which TC was the main contributor to TFP growth (Emvalomatis 2012;Keizer and Emvalomatis 2014;Marzec and Pisulewski 2019). Contradictory findings have been provided by Cechura et al (2017), who found that TC among dairy farms in the new EU member states was negative (from 2004 to 2011), except for that in the Czech Republic and Slovakia.…”
Section: Resultssupporting
confidence: 92%
“…Our results are in line with findings from other studies of European examples in which TC was the main contributor to TFP growth (Emvalomatis 2012;Keizer and Emvalomatis 2014;Marzec and Pisulewski 2019). Contradictory findings have been provided by Cechura et al (2017), who found that TC among dairy farms in the new EU member states was negative (from 2004 to 2011), except for that in the Czech Republic and Slovakia.…”
Section: Resultssupporting
confidence: 92%
“…This indicates that estimates of technical efficiency are sensitive to the assumption made regarding the type of distribution of inefficiency. This finding is supported by Marzec and Pisulewski (2019), who also analysed crop farms in Poland, but using a truncated-normal SF model and obtained a substantially lower mean technical efficiency score (63%).…”
Section: Resultsmentioning
confidence: 54%
“…Therefore, the ranking of farms is not affected by choice of distribution. Similarly, in the study conducted by Marzec and Pisulewski (2019), the correlation between half-normal and truncatednormal technical efficiency scores was high (0.99). The form of the production function makes as well little difference in the farms' rankings because the geometric mean of the Spearman correlations is equal to 0.95.…”
Section: Resultsmentioning
confidence: 73%
“…Rudinskaya et al, 2019, Quiroga et al, 2017, Zhu et al, 2008. Extended research using two or more efficiency assessment methods can be found in the papers of Kočišová, 2015;Hoang and Trung, 2013;Marzec, 2019;Vlontzos et al, 2017, and others.…”
Section: Technical Efficiency Of Agriculture In Scientific Researchmentioning
confidence: 99%